China Satellite Navigation Conference (CSNC) 2017 Proceedings: Volume III - Sun, Jiadong; Liu, Jingnan; Yang, Yuanxi; Fan, Shiwei; Yu, Wenxian (Lecture Notes in Electrical Engineering,, 2017)
These proceedings present selected research papers from CSNC2017, held during 23th-25th May in Shanghai, China. The theme of CSNC2017 is Positioning, Connecting All. These papers discuss the technologies and applications of the Global Navigation Satellite System (GNSS), and the latest progress made in the China BeiDou System (BDS) especially. They are divided into 12 topics to match the corresponding sessions in CSNC2017, which broadly covered key topics in GNSS. Readers can learn about the BDS and keep abreast of the latest advances in GNSS techniques and applications.